Peran Pemerintah Kabupaten Pangandaran Dalam Mengatasi Kemiskinan - Yuliyantini, Yuliyantini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The Poverty is still a problem for all regions in Indonesia including Pangandaran Regency which is a new autonomous region in West Java. The purpose of this study was to find out how the efforts made by the regional government of Pangandaran Regency to deal with the poor and how the results of the local government's role in dealing with the poor in Pangandaran Regency. The research method used is a qualitative descriptive method by researching and describing poverty in Pangandaran Regency in 2021 and 2022. The results of the research show that poverty in Pangandaran Regency has decreased, from 9.65 percent in 2021 to 9.32 percent only in 2022 or a decrease of around 0.33 percent, which means around 1,083 people are free from poverty in Pangandaran Regency. This is inseparable from the efforts made by Pangandaran Regency in the form of Providing Direct Assistance, Improving the Quality of Education, Development of New Tourist Destinations, Improving Facilities and Health Insurance, Development of Infrastructure Facilities, Development of Settlements.